Evaluation of Adverse Drug Reactions to Artemisininbased Combination Therapy in a Nigeria University Community (2008)
Purpose: The study was carried out to evaluate the incidence of adverse reactions to antimalarial drugs among residents of a Nigeria university community with a focus on artemisinin-based combination therapy (ACT). Specifically, the profile of use, and the reporting culture of people with respect to experienced reactions were noted. Method: Questionnaires were administered to respondents at the university health centre between November 2006 and January 2007. Information on demographic characteristics, nature of experienced adverse reactions and the most frequently used ACT, among other questions, were collected. Descriptive statistics and Fisher’s Exact test were used to evaluate the distribution of respondent’s opinion. Result: The study achieved a response rate of 86%. The results revealed that 210 (70.0 %) of respondents said they had used artemisinin-based combination drugs while 134 (44.7 %) said they used artemisinin derivatives alone as monotherapy for malaria treatment. Artesunate plus amodiaquine 94 (31.3%) as a co-packaged product was the most commonly used ACT. Incidence of the experienced adverse reactions to ACT was reported to be generally mild and well tolerated. Conclusion: Efforts to improve the use of ACT in the management of acute uncomplicated P. falciparum malaria is recommended. Furthermore, an effective mechanism to improve reporting of adverse effects of ACT is also recommended